Compromising the authority of international criminal justice: how Vojislav Šešelj runs his trial - Sluiter, Göran (Journal of international criminal justice, 2007)
`eaelj's conduct continues to cause major problems to the International Criminal Tribunal for the former Yugoslavia. The approach of both the Trial Chamber and the Appeals Chamber to the accused's hunger strike is a matter of serious concern. Especially the Appeals Chamber's decision leaves one with the impression that `eaelj is running his own trial. This note offers a critical analysis of the Trial Chamber's and Appeals Chamber's responses to the accused's hunger strike and their damaging implications